Forest machine automation and ergonomics - Sokolov Anton; Seliverstov Alexander; Sukhanov Yuri (E3S Web of Conferences, 2023)
Harvesters and forwarders are the main part of cut-to-length logging system equipment. The perfection of the hydraulic cranes has a very large impact on the overall operating efficiency of these forest machines. The impact of the crane partial automation on the operator’s work cycle and workload is described in this article. Two machines were studied in field conditions. Differences in the frequency and duration of telescopic extension boom control activations were identified. It was determined that, as a result of automation, one of the degrees of freedom of the crane controls is almost completely excluded from use in the case of the forwarder. A significant reduction in the duration of its use is observed in the case of the harvester. As a result, this saves the psycho-physiological resources of the operator for more efficient use of the remaining degrees of freedom, which, coupled with a simpler and more intuitive logic of the controls operation, improves the productivity, accuracy and safety of cut-to-length logging. In addition, a simpler work algorithm reduces the level of stereotyping of the operator’s actions, fatigue and loss of attention, which usually emerge at the end of the shift. This work was supported by the Russian Federation Ministry of Science and Higher Education (state research target, theme no. 075-03-2023-128).